Removal of Sodium Dodecylbenzenesulphonate and Cetyltrimethylammonium Bromide Using a Carbon Composite Derived from Modified Zn–Al-Layered Double Hydroxide - Rodrigo Morais Menezes dos Santos; Rosembergue Gabriel Lima Gonçalves; Marina de Carvalho Eufrásio Pinto; Roberta Gomes Prado; Vera Regina Leopoldo Constantino; Liovando Marciano da Costa; Frederico Garcia Pinto; Jairo Tronto (Adsorption Science & Technology)
We describe the synthesis of a composite carbon derived from zinc–aluminium-layered double hydroxides. The material was characterized by powder X-ray diffraction, Fourier transform infrared/attenuated total reflectance spectroscopy, thermogravimetric analysis–differential scanning calorimetry–mass spectrometry, measurement of BET specific surface area, zeta-potential analysis and scanning electron microscopy. The resulting material was used for adsorption studies with an anionic surfactant, sodium dodecylbenzenesulphonate, and a cationic surfactant, cetyltrimethylammonium bromide, as adsorbates. The adsorption of the surfactants was well described by the typical Langmuir pattern. An investigation of the influence of initial pH of a medium on surfactant adsorption showed that high pH values decrease the adsorption capacity of the adsorbent. The adsorption processes were exothermic. The results also showed that the adsorption of the two surfactants was chemical and that the kinetic models were best described by a pseudo-second-order model.